DISCUSSING ON ANITA DESAI’S CONTRIBUTION TO INDIAN WRITING IN ENGLISH NOVELS - N.K.Gosain; Kaur, Komalpreet (International Journal of Psychosocial Rehabilitation, 2020)
Anita Desai is one of India’s most well-known and creative novelists. On the 24th of June 1937, she was born in Mussorie, India. Her father was Bengali, while her mother was German. She spoke English, Hindi, Bengali, and German as a child. Her first language was English. She began writing in English when she was seven years old. She’s written books, stories, children’s books, and essays. Desai was up speaking English, German, and Hindi, but it was at Queen Mary’s Higher Secondary School in New Delhi that she learned to read and write in English. As a result, when she was seven years old, she began writing in English. "At home, we spoke German, and that’s how I learnt nursery rhymes and fairy tales." With all of our friends and neighbours, we spoke Hindi. When I was in school, I studied English." Desai went on to Miranda House, a world-class school of Delhi University, where she earned her B.A. in English Literature in 1957. She began her abstract career at the age of seven, and her first tale was published when she was nine years old. Sri. Aswin Desai, the CEO of a computer software company, was her husband. They had four children together. In 1986, she was a meeting individual at Cambridge University’s Girton College. She attended Smith College from 1987 to 1989. Desai’s first publication was a tale in a children’s magazine in the United States. She issued twelve fiction works as well as a variety of expositions, audits, and essays. Apart from Games of Twilight (1978), an anthology of stories, the remaining works are books, three of which are for children. She is frequently referred to as a "Feminist" and a "Mental Novelist." In her novels, she discusses estrangement, intellectual journeys, and humanistic character. She portrays modern emergency and confrontations between two shafts of human experience, social and heavenly mission, as a cutting edge and post autonomous lady. "The anxiety of confronting, isolated, the fierce attacks of presence," Desai describes the central theme of her fiction. She is frequently regarded as a feminist mental writer who addresses key issues such as solitude, lack of correspondence, psychological struggle, man-woman relationships, and conjugal difficulties. Her heroines are all women. Anita Desai’s language and tactics vary depending on the issue and situation. She employs Nostalgia, or recollections of the past, as an account approach. Her distinct style of writing, distinct characters, language use, practical theme, and account approach have made her writing so appealing that she has received numerous accolades, awards, and grants for her work. Her dedication to the academic community is unquestionable. All areas of her composing are examined in the paper.